2009
DOI: 10.1080/10739140903088160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Methods for Determination of Arsenic in Coal and Coal Ash

Abstract: In this paper the comparative analysis of different methods for the preparation and analysis of arsenic content in coal and coal ash have been presented. The suggested method is coal digestion method, i.e., coal ash digestion using the mixture of acids: nitric and sulphuric in presence of vanadium-pentoxide as catalyzer. The comparative analysis of different recording techniques (AAS-GH, AAS-GF and ICP-AES) has also been presented. For arsenic recording the suggested technique is AAS-GF technique. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…40 Analytical methods for determining different arsenic species have become increasingly important due to the different toxicity and chemical behaviour of the various arsenic forms. Well-established methods that involve the coupling of separation techniques, such as ion chromatography (IC) 41,42 and high performance liquid chromatography (HPLC) 43,44 with a sensitive detection system, such as inductively coupled plasma-mass spectrometry (ICP-MS), 6 hydride generation-atomic fluorescence spectrometry (HG-AFS), hydride generation-atomic absorption spectrometry (HG-AAS) 45 and graphite furnace-atomic absorption spectrometry (GF-AAS) 46 are the methods of choice for the routine determination of a large number of water samples. A compilation of the developed methods commonly employed in speciation analyses is provided in Table S-II of the Supplementary material.…”
Section: Analytical Methods For Speciation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…40 Analytical methods for determining different arsenic species have become increasingly important due to the different toxicity and chemical behaviour of the various arsenic forms. Well-established methods that involve the coupling of separation techniques, such as ion chromatography (IC) 41,42 and high performance liquid chromatography (HPLC) 43,44 with a sensitive detection system, such as inductively coupled plasma-mass spectrometry (ICP-MS), 6 hydride generation-atomic fluorescence spectrometry (HG-AFS), hydride generation-atomic absorption spectrometry (HG-AAS) 45 and graphite furnace-atomic absorption spectrometry (GF-AAS) 46 are the methods of choice for the routine determination of a large number of water samples. A compilation of the developed methods commonly employed in speciation analyses is provided in Table S-II of the Supplementary material.…”
Section: Analytical Methods For Speciation Analysismentioning
confidence: 99%
“…100,101 Digestion using the mixture of acids: nitric and sulphuric in presence of vanadium pentoxide as catalyst is a powerful technique for the separation and determination of arsenic in coal and coal ash. 46,102 Giacomino et al 103 investigated the fractionation and speciation of As in contaminated soil. Regarding speciation, they found that As(V) prevailed over As(III), while more than 40 % of total arsenic was in an organic form.…”
Section: Sample Extractionmentioning
confidence: 99%
“…The chemical composition of the materials was determined by standard silicate analysis. 23,24 1440 JOVANOVIĆ et al…”
Section: Materials and Characterization Techniquesmentioning
confidence: 97%
“…Od analitičkih metoda za kvantifikaciju arsena u vodi, koje je odobrila Američka agencija za zaštitu životne sredine (eng. Environmental Protection Agency, EPA), najčešće se primenjuje metoda atomske apsorpcije generisanih hidrida [7].…”
Section: Metode Detekcije I Kvantifikacije Arsena U Akvatičnim Sistemimaunclassified